All New Faces of Diatoms: Potential Source of Nanomaterials and Beyond - Mishra, Meerambika; Arukha, Ananta P.; Bashir, Tufail; Yadav, Dhananjay; Prasad, G. B. K. S. (Frontiers in Microbiology, 2017)
Nature’s silicon marvel, the diatoms have lately astounded the scientific community with its intricate designs and lasting durability. Diatoms are a major group of phytoplanktons involved in the biogeochemical cycling of silica and are virtually inherent in every environment ranging from water to ice to soil. The usage of diatoms has proved prudently cost effective and its handling neither requires costly materials nor sophisticated instruments. Diatoms can easily be acquired from the environment, their culture requires ambient condition and does not involve any costly media or expensive instruments, besides, and they can be transported in small quantities and proliferated to a desirable confluence from that scratch, thus are excellent cost effective industrial raw material. Naturally occurring diatom frustules are a source of nanomaterials. Their silica bio-shells have raised curiosity among nanotechnologists who hope that diatoms will facilitate tailoring minuscule structures which are beyond the capabilities of material scientists. Additionally, there is a colossal diversity in the dimensions of diatoms as the frustule shape differs from species to species; this provides a scope for the choice of a particular species of diatom to be tailored to an exacting requisite, thus paving the way to create desired three dimensional nanocomposites. The present article explores the use of diatoms in various arenas of science, may it be in nanotechnology, biotechnology, environmental science, biophysics or biochemistry and summarizes facets of diatom biology under one umbrella. Special emphasis has been given to biosilicification, biomineralization and use of diatoms as nanomaterial’s, drug delivery vehicles, optical and immune-biosensors, filters, immunodiagnostics, aquaculture feeds, lab-on-a-chip, metabolites, and biofuels.